2007
DOI: 10.1001/archderm.143.12.1559
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Psoriasis in the General Population

Abstract: To study the clinical spectrum of psoriasis and the incidence in the general population and to identify risk factors associated with the occurrence of psoriasis.Design: Prospective cohort study with nested casecontrol analysis. Setting:The data source was the United Kingdom General Practice Research Database containing computerized clinical information entered by general practitioners (GPs). Patients:The study population comprised patients receiving a first-ever diagnosis of psoriasis between January 1, 1996, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
268
7
19

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(310 citation statements)
references
References 39 publications
16
268
7
19
Order By: Relevance
“…High quality publications found smoking to be an independent risk factor for psoriasis, with risk of psoriasis higher in exsmokers and current smokers than never smokers. 58,59 A marked dose-response relationship exists; the risk for development of psoriasis is highest for people smoking more than 20 cigarettes/day. 60 A similar dose-response relationship was confirmed for those smoking more than 15 cigarettes/day.…”
Section: -52mentioning
confidence: 99%
See 1 more Smart Citation
“…High quality publications found smoking to be an independent risk factor for psoriasis, with risk of psoriasis higher in exsmokers and current smokers than never smokers. 58,59 A marked dose-response relationship exists; the risk for development of psoriasis is highest for people smoking more than 20 cigarettes/day. 60 A similar dose-response relationship was confirmed for those smoking more than 15 cigarettes/day.…”
Section: -52mentioning
confidence: 99%
“…They also had a higher prevalence of hypertriglyceridemia and abdominal obesity, whereas hyperglycemia, HTN, and HDL levels were similar. Although psoriasis patients were more frequently smokers, the association of psoriasis with metabolic syndrome was independent from smoking 7 of 9 58 …”
mentioning
confidence: 94%
“…57 A Spanish study reported a group of young subjects (21-40 years) who had upper respiratory tract infections before onset of psoriasis. 58 Some Chinese studies have shown similar findings. 9,12,17 Infection is the most common trigger for childhood psoriasis, which is consistent with the findings of Wu et al and Chiam et al regarding Chinese, Dutch, and Singaporean psoriasis studies.…”
Section: Infectionmentioning
confidence: 69%
“…The disease affects 4% of all children younger than 16 years with all types of dermatologic disorders (2)(3)(4). The onset of disease in one third of all patients in childhood is in the first and second decades of life and there is a strong association between early onset of disease and HLA-Cw6 (5).…”
Section: Contextmentioning
confidence: 99%
“…The onset of disease in girls is earlier than boys (7,8). Psoriasis is a chronic cell mediated inflammatory disease characterized by keratinocyte hyperproliferation, vascular endothelial proliferation and inflammatory cell infiltration of dermis and epidermis, with many of pathogenic mechanisms not fully cleared yet (1)(2)(3)(4). Several factors are contributed as causative agents of disease including genetic, environmental and immunologic factors (9).…”
Section: Contextmentioning
confidence: 99%